2021
DOI: 10.1186/s41938-020-00353-7
|View full text |Cite
|
Sign up to set email alerts
|

Role of host diet on the fitness of the egg parasitoid species, Trichogramma evanescens Westwood (Hymenoptera: Trichogrammatidae)

Abstract: Background Egg parasitoids belonging to the genus Trichogramma (Hymenoptera: Trichogrammatidae) are important natural enemies that have been successfully used in biological control programs and mostly reared on the Mediterranean flour moth, Ephestia kuehniella (Zeller) (Lepidoptera: Pyralidae). Host quality is a crucial factor that can determine parasitoid fitness. Main body Laboratory studies were carried out to evaluate the effects of 3 different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“… Kurtuluş et al (2019) showed that addition of several components to diets, such as nutritional yeast and wheat bran, can shorten the development time of E. kuehniella and increase its fertility because of the correct balance of nutrients and minerals. Addition of wheat bran, glycerin, and yeast to E. kuehniella diets gave similar results, significantly shortening the development time compared with diets based only on corn meal and yeast ( Pehlivan 2021 ).…”
Section: Discussionmentioning
confidence: 86%
“… Kurtuluş et al (2019) showed that addition of several components to diets, such as nutritional yeast and wheat bran, can shorten the development time of E. kuehniella and increase its fertility because of the correct balance of nutrients and minerals. Addition of wheat bran, glycerin, and yeast to E. kuehniella diets gave similar results, significantly shortening the development time compared with diets based only on corn meal and yeast ( Pehlivan 2021 ).…”
Section: Discussionmentioning
confidence: 86%
“…Although Trichogramma parasitoids are usually generalists, many species could not successfully reared their offspring using COS eggs, such as Trichogramma ostrinia, which can complete its development inside COS eggs but is unable to form an emergence hole due to the thick shells of COS eggs, resulting in the death of the parasitized wasps inside the eggs [15]. Several studies have reported varying suitability of Trichogramma for different hosts; characteristics such as host egg size, eggshell thickness, nutrients of the host egg fluid, and host age affect Trichogramma parasitism [16][17][18]. These factors often play a crucial role in determining the suitability of factitious hosts for mass production; as a result, the selection of suitable factitious hosts for biological control is of vital importance.…”
Section: Introductionmentioning
confidence: 99%